BUDAYA PATRIARKI DALAM NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL-SAADAWI DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Nessa Izzati Aulia; Mohamad Zaenal Arifin; Dede Ibrahim (Institut Binamadani Indonesia, 2026)
This study aims to explore the forms of patriarchal culture that are explicitly contained in the novel Perempuan di Titik Nol by Nawal El Sadaawi. Most patriarchal systems generally place men in high-ranking roles and possess dominant authority within the social order. This has a significant impact on the marginalization of women's status and contributions. This research is qualitative with a descriptive analytical approach. Primary data was obtained from Nawal El-Saadawi's novel